Effect of spinal irradiation on growth. Issue 5 (May 1987) - Shalet, S M; Gibson, B; Swindell, R; Pearson, D
Abstract : Standing height, sitting height, and leg length were measured in 79 patients (aged 16-30 years), who had been given craniospinal irradiation (n = 37) or cranial irradiation (n = 42) in childhood for a brain tumour and had completed their growth. Their measurements were compared with established standards for sitting height and leg length in British children (aged 16-18 years). To examine the effects of spinal irradiation on spinal growth independent of growth hormone deficiency we analysed the leg length (LL) minus sitting height (SH) standard deviation score (SDS) and used the cranial group as controls. There was an overall significant difference between the median craniospinal LL-SH SDS (1.98) and the median cranial LL-SH SDS (0.545). Within the craniospinal group there was a significant correlation with age at treatment, but there was no such correlation for the cranial group. After splitting age at treatment into three groups (0 less than 5, 5 less than 10, and 10-15 years) there was a significant difference between the LL-SH SDS of the craniospinal and cranial groups for each of the age ranges. In conclusion, spinal irradiation has a profound effect on spinal growth and the younger the child is when given irradiation the greater the subsequent skeletal disproportion. Our most conservative figures indicate that the eventual loss in height is 9 cm when irradiation is given at 1 year, 7 cm when given at 5 years, and 5.5 cm when given at 10 years.